Akuntabilitas Publik dalam Penanganan Kecelakaan Kapal melalui Operasi SAR: Studi Kasus Kantor Pencarian dan Pertolongan Gorontalo - Malasari; Irawaty Igirisa; Juriko Abdussamad (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2025)
This study aims to analyze public accountability in the Gorontalo Search and Rescue (SAR) Office across five dimensions: performance, financial, legal, moral, and innovation. These dimensions are theoretically anchored in Bovens’ multidimensional accountability framework, which distinguishes procedural, professional, and outcome-based responsibilities; this grounding clarifies the conceptual meaning and analytical basis of each dimension. Accountability is viewed as a central pillar of institutional legitimacy, especially in crisis settings where public expectations are heightened. A descriptive qualitative approach was employed, supplemented by a structured quantitative scoring procedure. Qualitative indicators derived from interviews, observations, and document analysis were converted into numerical values using predefined rubrics aligned with the accountability framework, allowing transparent and non-arbitrary visualization through radar and bar charts. Findings show that moral accountability received the highest score, reflecting strong humanitarian responsibility, emotional support to victims’ families, and dignified victim handling. Performance accountability also scored well, supported by response speed, procedural compliance, and inter-agency coordination, although resource constraints limited operational effectiveness. Financial and legal accountability demonstrated moderate results, indicating persistent tensions between bureaucratic compliance and operational flexibility. Innovation accountability was the weakest dimension due to limited adoption of advanced technologies such as drones, satellite-based communication, and digital dashboards.Overall, the study indicates that the Gorontalo SAR Office has established a credible accountability foundation but requires strengthened innovation capacity and improved regulatory harmonization. By explicitly grounding the five accountability dimensions in a recognized theoretical framework and employing a transparent qualitative-to-quantitative scoring process, this study offers a more analytically rigorous contribution to understanding accountability within crisis-response institutions in developing countries.